Taxonomic revision of the genus Chileanthicus Werner (Coleoptera: Anthicidae) - Kejval, Zbyněk (Zootaxa, 2009)
Chileanthicus Werner, 1966 is redescribed and its position within Formicomini Bonadona, 1974 is briefly discussed. Twelve previously known species are redescribed: Chileanthicus dentatus (Dajoz, 1980), C. dentivarius (Lea, 1922), C. interruptus (Lea, 1922), C. kingii (MacLeay, 1872), C. lafertei (Solier, 1851), C. latibasis (Lea, 1922), C. mastersii (King, 1869), C. melasomus (Lea, 1922), C. penai Werner, 1966, C. pubifasciatus (Lea, 1922), C. quadrimaculatus (King, 1869), C. speciosus (King, 1869). Thirty species are newly described: Chileanthicus acutipennis sp. nov., C. baculentus sp. nov., C. elmorado sp. nov., C. femineus sp. nov., C. hirsutus sp. nov., C. maritimus sp. nov., C. mitis sp. nov. (all Chile), C. cursor sp. nov. (Madagascar), C. angulicollis sp. nov., C. aprilis sp. nov., C. audax sp. nov., C. campicola sp. nov., C. comes sp. nov., C. communis sp. nov., C. decipiens sp. nov., C. discus sp. nov., C. exul sp. nov., C. eyrensis sp. nov., C. gammon sp. nov., C. improvidus sp. nov., C. inflatus sp. nov., C. insignis sp. nov., C. kinchega sp. nov., C. matthewsi sp. nov., C. paganus sp. nov., C. pulcher sp. nov., C. pumilio sp. nov., C. tuberculifer sp. nov., C. uhmanni sp. nov., C. volselifer sp. nov. (all Australia). Eleven new combinations are proposed: Chileanthicus dentivarius (Lea, 1922) comb. nov., C. interruptus (Lea, 1922) comb. nov., C. kingii (MacLeay, 1872) comb. nov., C. latibasis (Lea, 1922) comb. nov., C. mastersii (King, 1869) comb. nov., C. melasomus (Lea, 1922) comb. nov., C. pubifasciatus (Lea, 1922) comb. nov., C. quadrimaculatus (King, 1869) comb. nov., C. speciosus (King, 1869) comb. nov. and C. tridentipes (Lea, 1922) comb. nov. (all from Formicomus LaFerté-Sénectère, 1849), and Chileanthicus dentatus (Dajoz, 1980) comb. nov. (from Pseudoleptaleus Pic, 1900). New synonymy, Chileanthicus mastersii (King, 1869) (= Formicomus tridentipes Lea, 1922 syn.nov.), is proposed. Lectotypes are designated for Formicomus mastersii King, 1869 and F. melasomus Lea, 1922. All known species of Chileanthicus are listed and a key to their identification is provided.